Case report: Hereditary spastic paraplegia with a novel homozygous mutation in ZFYVE26 - Lai, Ze-hua; Liu, Xiao-ying; Song, Yuan-yue; Zhou, Hai-yan; Zeng, Li-li (Frontiers in Neurology, 2023)
Hereditary spastic paraplegia (HSP) is a group of neurodegenerative diseases with genetic and clinical heterogeneity characterized by spasticity and weakness of the lower limbs. It includes four genetic inheritance forms: autosomal dominant inheritance (AD), autosomal recessive inheritance (AR), X-linked inheritance, and mitochondrial inheritance. To date, more than 82 gene loci have been found to cause HSP, and SPG15 (ZFYVE26) is one of the most common autosomal recessive hereditary spastic paraplegias (ARHSPs) with a thin corpus callosum (TCC), presents with early cognitive impairment and slowly progressive leg weakness. Here, we reported a homozygous pathogenic variant in ZFYVE26. A 19-year-old Chinese girl was admitted to our hospital presenting with a 2-year progressive bilateral leg spasticity and weakness; early cognitive impairment; corpus callosum dysplasia; chronic neurogenic injury of the medulla oblongata supplied muscles; and bilateral upper and lower limbs on electromyogram (EMG). Based on these clinical and electrophysiological features, HSP was suspected. Exome sequencing of the family was performed by high-throughput sequencing, and an analysis of the patient showed a ZFYVE26 NM_015346: c.7111dupA p.(M2371Nfs*51) homozygous mutation. This case reported a new ZFYVE26 pathogenic variant, which was different from the SPG15 gene mutation reported earlier.